Methodology to Track Incremental Adaptation in Smallholder Farmers' Livelihood Changes in Wolaita Zone, Ethiopia - Fanta, Workneh; Gibbons, Pat; Kuma, Berhanu (Sustainable development (Bradford, West Yorkshire, England), 2025)
Wolaita zone, like most other Ethiopian zones, is subject to top‐down policy formulation with limited opportunities to engage with local populations. This is at odds with conventional thinking that seeks to “value” local knowledge and experience. This study aims to address this anomaly by building a rich baseline on livelihood practices and locally experienced adaptation strategies elicited from 400 households and six districts of the zone. The study was designed to accommodate agroecologies and technologies (GPS) to overcome challenges associated with changing farm ownership and kebele boundaries. The researcher can go back to the same 400 locations at 2‐year intervals to monitor livelihood changes and to ascertain the rationale for these changes. Data are analyzed using the linear mixed‐effects models to compare the level of changes and causes. It is anticipated that this methodology will significantly contribute to providing policymakers with evidence‐based and up‐to‐date information continuously.